2008
DOI: 10.1109/tmi.2008.923696
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis and Improvement of SIRT

Abstract: Iterative X-ray computed tomography (CT) algorithms have the potential for producing high-quality images but are computationally very demanding, especially when applied to high-resolution problems. Focusing on simultaneous iterative reconstruction technique (SIRT), we provide an eigenvalue based scheme for automatically determining a near-optimal value of the relaxation parameter. This accelerates the convergence rate of SIRT to the point where only half the number of iterations normally required is needed. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 21 publications
0
133
0
1
Order By: Relevance
“…(3) SIRT (Simultaneous Iterative Reconstruction Technique) is an algebraic technique that computes a weighted least squares solution of (1) [13]. SIRT was implemented as defined in [14], performing 300 iterations. (4) PDART [15] (Partially Discrete Algebraic Reconstruction Technique) is a partially discrete technique that assumes that only the densest material is homogeneous.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…(3) SIRT (Simultaneous Iterative Reconstruction Technique) is an algebraic technique that computes a weighted least squares solution of (1) [13]. SIRT was implemented as defined in [14], performing 300 iterations. (4) PDART [15] (Partially Discrete Algebraic Reconstruction Technique) is a partially discrete technique that assumes that only the densest material is homogeneous.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…1 (a), an example of the cupping artifact is given. It is a 2D cross section of an Au-Ag core-shell nanoparticle [7] , reconstructed using the SIRT algorithm [8] . If we look at the line-profile of the 2D image ( Fig.…”
Section: E-mail Address: Zhong@cwinl (Z Zhong)mentioning
confidence: 99%
“…The reconstruction is computed using the simultaneous iterative reconstruction technique (SIRT) [8] which solves the following least-squares problem:…”
Section: The Correction Algorithmmentioning
confidence: 99%
“…In our implementation, the basic algorithm for computing a real-valued surrogate solution is the iterative SIRT algorithm [18], defined as follows. Let…”
Section: Surrogate Solutionsmentioning
confidence: 99%
“…It can be shown that for a consistent system of equations, the SIRT-algorithm as described in Eq. (6) converges to the solutionṽ that is closest to the initial image v (0) with respect to a certain norm (a weighted sum of squares, see [18]). Here, we use an adaptation of this algorithm which confines the solution to the interval [0, 1].…”
Section: Surrogate Solutionsmentioning
confidence: 99%